Cost management: a realistic and updated approach (Costos y Gestión, 2025)
This paper aims at introducing current state of business practice regarding costing models and cost management, proposing application of "multiple costing" concept, in line with importance of effective cost utilization in business management, far above simply calculating costs. Methodology used in this work consists of theoretical research based on existing literature, complemented by results of fieldwork and conclusions drawn from professional experience and practice.Costing practices in different countries, such as USA, Germany, Japan, and China, show their own perspectives with varying nuances, although absorption costing models, standard costing, cost-volume-profit analysis, cost reduction as a prioritized strategic imperative, and usage of information to increase competitiveness and improve profitability are widely applied today. Technological advances create new processes and operational models, just as high-speed information technology generates abundant data, and Artificial Intelligence modifies processes and activities, with a wide range of concrete practical applications as John Deere and Domino's Pizza cases reveal.
Keywords: artificial intelligence; costing models; costs management; cost reduction